2019
DOI: 10.4269/ajtmh.18-0585
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Survey of Bartonella Species in Shelter Cats in Rio De Janeiro: Clinical, Hematological, and Risk Factors

Abstract: The present study aimed to detect Bartonella DNA in cats belonging to shelters, and to evaluate risk factors, clinical signs, and hematological abnormalities associated with infection. Complete blood counts and screening for the presence of Bartonella DNA were performed on cats' ethylenediamine tetraacetic acid anticoagulant-blood samples. Eighty-three cats (39.9%) were positive for Bartonella species. Bartonella DNA was also detected in fleas and in the blood of cats infested by positive flea. Cats that had n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 40 publications
3
18
0
Order By: Relevance
“…Previously, a small Bartonella-gltA sequence fragment (96-bp) sharing 99% identity with B. koehlerae was detected in a margay (L. wiedii) maintained in captivity in a Brazilian zoo (FILONI et al, 2012). Recently, B. koehlerae was detected in cats in Rio de Janeiro (RAIMUNDO et al, 2019). Although B. koehlerae has been isolated from cat blood, the routes of transmission among cats have not been fully established yet (PENNISI et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, a small Bartonella-gltA sequence fragment (96-bp) sharing 99% identity with B. koehlerae was detected in a margay (L. wiedii) maintained in captivity in a Brazilian zoo (FILONI et al, 2012). Recently, B. koehlerae was detected in cats in Rio de Janeiro (RAIMUNDO et al, 2019). Although B. koehlerae has been isolated from cat blood, the routes of transmission among cats have not been fully established yet (PENNISI et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The overall prevalence of Bartonella DNA was 47.5% in cat blood, 18.3% in eas, 13.3% in ea egg pools, and 12.5% in lice pools. The occurrence of Bartonella DNA was higher than previously reported, especially in shelter cats [19][20][21][22][23][24][25]. However, a previous study reported 97.3% positivity in one shelter in Rio de Janeiro, Brazil [26].…”
Section: Discussionmentioning
confidence: 67%
“…Considering the ea importance on Bartonella transmission between cats [9,25] and the absent link of lice infestation to Bartonella infection in cats in this and previous studies [25,30], it is necessary to be cautious to infer that the louse was responsible for the transmission of bacteria to the cat in the present study. In order to analyse the importance of the lice as a vector of Bartonella spp.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations